2010
DOI: 10.1007/s10669-010-9268-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the gene expression changes in Nile tilapia (Oreochromis niloticus) as affected by the bio-removal of toxic textile dyes from aqueous solution in small-scale bioreactor

Abstract: A laboratory-scale bioremediation unit was designed, built and tested for the bio-removal of several Direct textile dyes. Four experiments were carried out to assess the efficiency of the bioremediation unit using Aspergillus niger fungal strain. Three commonly used Direct dyes and textile dyes mixture (simulated effluent: Direct brown, Direct violet, Direct green) were tested in this study. The strain of A. niger was efficient in the removal of the three Direct dyes. The decolorization percentages of the dyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Mohanty et al ( 85 ) demonstrated that it is a sensitive indicator of exposure of aquatic animals to different pollutants and causes an abnormal increase of proteins in the nucleus and cytosol ( 86 , 87 ). Due to trace elements contamination, Hsp70 protein bands in muscle tissues of Nile tilapia caught from Mariout and Abbassa was obvious but absent in muscle tissues of Nile tilapia caught from Aswan ( Figure 3A ), similar to AbdEl-Rahim et al ( 88 ) and Deen ( 89 ). The expression of Hsp70 was upregulated in the liver ( Figures 3A,B ) because it is responsible for the accumulation and detoxification of toxins ( 90 ) and performs multiple key functions as energy metabolism.…”
Section: Discussionsupporting
confidence: 81%
“…Mohanty et al ( 85 ) demonstrated that it is a sensitive indicator of exposure of aquatic animals to different pollutants and causes an abnormal increase of proteins in the nucleus and cytosol ( 86 , 87 ). Due to trace elements contamination, Hsp70 protein bands in muscle tissues of Nile tilapia caught from Mariout and Abbassa was obvious but absent in muscle tissues of Nile tilapia caught from Aswan ( Figure 3A ), similar to AbdEl-Rahim et al ( 88 ) and Deen ( 89 ). The expression of Hsp70 was upregulated in the liver ( Figures 3A,B ) because it is responsible for the accumulation and detoxification of toxins ( 90 ) and performs multiple key functions as energy metabolism.…”
Section: Discussionsupporting
confidence: 81%
“…The total RNA was used as a template for cDNA synthesis. As described by AbdEl-Rahim et al (2010) , DNase I-treated RNA (2 μg) was reverse transcribed to cDNA using oligo (dT) and random hexamer primers with the reverse transcriptase enzyme of Super-Script II (Invitrogen, United States). The amplified cDNA was used as a template for qRT-PCR through sets of PR primers ( Table 1 ) with β-actin gene (housekeeping gene) to normalize the transcription levels.…”
Section: Methodsmentioning
confidence: 99%
“…SPECTROstar Nano was used to determine the purity and concentration of extracted RNA (BMG Labtech, Ortenberg, Germany). As previously described ( AbdEl-Rahim et al, 2010 ; Abdelkhalek et al, 2019 ), the isolated RNA was utilized to generate cDNA using a reverse transcriptase (RT) enzyme. In an Eppendorf cycler (Hamburg, Germany), the RT reaction was conducted at 42°C for 1 h and then deactivated at 80°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%